Desain dan Tata Letak Buku Cerita Anak dari Pegunungan Tengah Indonesia Timur - Andreas James Darmawan; Elizabeth Jessica Sentani; Segah Natalleo; Karin Cinthya Putri; Eunike Yolanda Zefanya Sitinjak (Jurnal Pengabdian kepada Masyarakat Bidang Ilmu Komputer, 2025)
This community service initiative arose from concerns about the low basic literacy skills of children in the Central Highlands region of Eastern Indonesia. This region faces the challenge of limited contextual and engaging reading materials for young children, which impacts low reading and writing skills from elementary school age (Choiriyah et al., 2023). Through a collaboration between the Visual Communication Design (VCD) Study Program of Jakarta International University (JIU) and the humanitarian organization Wahana Visi Indonesia (WVI), this activity aims to help improve children's literacy skills through children's storybooks designed in an attractive, educational, and culturally appropriate manner. This project resulted in six quadrilingual children's storybooks (in Indonesian, English, Japanese, and Korean), written by six teachers from the Central Highlands and designed by the JIU VCD team consisting of lecturers and students. The activity process took place from August 2025 to January 2026, with a series of stages ranging from coordination, sketching, layout design, translation, and finalization. The event concluded with a publication at the 2025 National Seminar on Community Service in Computer Science (SENABDIKOM) and an exhibition of the work at the World Computer Science Conference (WVI). This event demonstrated the effectiveness of cross-disciplinary collaboration between visual communication design, language, and humanitarian organizations in creating learning media that supports children's literacy development.